Analisis Pemakaian Energi Pada Sensor Node Dengan Protokol Komunikasi RF24 Menggunakan Sumber Daya Baterai - Arya Sena Marga Mukti; Rakhmadhany Primananda; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Wireless Sensor Network (WSN) is a monitoring technology consisting of two or more sensor nodes scattered and coordinated by a system using a wireless network. The sensor node is a WSN constituent component that has a special section for sending and receiving data, one of which is the NRF24L01 module. One of the problems that occur in the sensor node is that with only limited resources such as batteries, the sensor node is expected to be capable of continuously running various processes. For that reason, the researcher builds sensor node equipped with NRF24L01 module and performs the measurement of energy consumption from the sensor node by direct observation using power monitor, thus producing sensor node which can be measured its power consumption, and to know the energy consumption of NRF24L01 application on the sensor node. Measurements are made through 3 scenarios, namely temperature data reading, data transmission, and temperature data readings as well as sending them. the effect is seen when the temperature data reading scenario, energy consumption of the sensor node is 58mAh, but when added data transfer process which involves NRF24L01 as communication module, energy consumption from sensor node to 75mAh.